Đánh giá mức độ ổn định vùng Tây Bắc đới đứt gãy Sông Hồng trên cơ sở phân vùng địa động lực - Anh, Lại Huy (Vietnam Journal of Earth Sciences, 2000)
Evaluation of the stable level for north-western region of the Red River Fault Zone based on geodinamic zonation